Pro-resolving lipid mediators in the resolution of neointimal hyperplasia pathogenesis in atherosclerotic diseases. (4th March 2019) - Satish, Mohan; Agrawal, Devendra K
ABSTRACT: Introduction : Despite advances in drug eluting technologies, neointimal hyperplasia (NIH) and restenosis still plagues endovascular therapy in atherosclerotic diseases. By appreciating atherosclerosis and NIH as complex inflammatory processes, specialized pro-resolving mediators (SPMs) are a superfamily of endogenous unsaturated fatty-acid derived lipids with the potential for inflammatory resolution. Areas covered : Inquiry into SPMs in this context is a novel approach and is the focus of this review, with emphasis on our understanding with NIH. Prior mechanistic understandings of SPM deficiency with atherosclerosis has offered insight, as well as the complexity and diversity of the SPM superfamily. Therapeutic investigation using SPMs to combat NIH is also evaluated here. Expert commentary : Endogenous deficiency of SPMs synthesis by 12/15-lipoxygenase underlies resolution deficits in atherosclerosis and NIH. Upstream PDGF inhibition by SPMs, most notably RvD1 and LXA4, confers a multifactorial attenuation of NIH that involves interconnected anti-inflammatory efforts, most notably switch pro-resolving smooth muscle cells (vSMCs) and macrophages. The ALX/FPR2 is one receptor system identified on vSMCs that interacts with these SPMs to promote NIH resolution. Therapeutically, while shown to be promising with less stent burden or cytotoxicity, SPMs must be balanced by necessary mechanistic, pharmacokinetic and anatomical considerations.